1999
DOI: 10.1094/mpmi.1999.12.10.882
|View full text |Cite
|
Sign up to set email alerts
|

The Alfalfa (Medicago sativa) TDY1 Gene Encodes a Mitogen-Activated Protein Kinase Homolog

Abstract: Development of root nodules, specifically induction of cortical cell division for nodule initiation, requires expression of specific genes in the host and microsymbiont. A full-length cDNA clone and the corresponding genomic clone encoding a MAP (mitogen-activated protein) kinase homolog were isolated from alfalfa (Medicago sativa). The genomic clone, TDY1, encodes a 68.9-kDa protein with 47.7% identity to MMK4, a previously characterized MAP kinase homolog from alfalfa. TDY1 is unique among the known plant MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 58 publications
1
25
0
Order By: Relevance
“…Induction of MAP kinases by fungal elicitors has been shown (Ligterink et al, 1997;Lebrun-Garcia et al, 1998) and transcripts of the MAP kinase gene Tdy1 was predominantly detected in the parenchymatic and meristematic regions of the nodule (Schoenbeck et al, 1999). The cDNA fragment identified here shows 100% identity on the nucleic acid level to a MAP kinase gene which can be detected in all tissues of P. sativum (Stafstrom et al, 1993) and which is involved in cell cycle regulation in Medicago sativa (Jonak et al, 1993).…”
Section: Ephmentioning
confidence: 65%
“…Induction of MAP kinases by fungal elicitors has been shown (Ligterink et al, 1997;Lebrun-Garcia et al, 1998) and transcripts of the MAP kinase gene Tdy1 was predominantly detected in the parenchymatic and meristematic regions of the nodule (Schoenbeck et al, 1999). The cDNA fragment identified here shows 100% identity on the nucleic acid level to a MAP kinase gene which can be detected in all tissues of P. sativum (Stafstrom et al, 1993) and which is involved in cell cycle regulation in Medicago sativa (Jonak et al, 1993).…”
Section: Ephmentioning
confidence: 65%
“…27,28 One another study showed that a gene called TDY1, believed to encode a MAPK homolog, was involved in root nodulation and root-tip development in Medicago. 29 One of the well-studied MAPKs in legumes is MAPK4 ortholog in soybean: this gene is involved in negative regulation of defense mechanism while in positive regulation of growth and development. 30 MAPKs in legumes are known to involve in various signaling responses that involve root organogenesis-for example, in Lupinus albus, activation of MAPKs such as SIMK and SAMK are required for infection of Bradyrhizobia sp.…”
Section: Introductionmentioning
confidence: 99%
“…To date, no mutant phenotypes have been ascribed to any MAP kinase gene of Arabidopsis or of any other plant. However, several plant MAP kinases have been identified that are activated by pathogen infection and by related signal molecules (35)(36)(37)(38)(39)(40)(41). For example, the tobacco MAP kinase SIPK is activated by tobacco mosaic virus infection, SA, by several pathogen-derived elicitors and by wounding (42)(43)(44).…”
Section: Identification Of Edr1 Orthologs In Crop Speciesmentioning
confidence: 99%